2015
DOI: 10.2174/1570161113666150827124714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micronized Purified Flavonoid Fraction Therapy on Endothelin-1 and TNF-α Levels in Relation to Antioxidant Enzyme Balance in the Peripheral Blood of Women with Varicose Veins

Abstract: We demonstrate the ability of MPFF to effectively lower the levels of ET-1 and TNF-α in patients with chronic venous disease. Further investigations are needed to define the therapeutic potential of MPFF including the potential effect on chronic subclinical inflammation, antioxidant imbalance and vascular dysfunction during the development of chronic venous disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
6
0
8
Order By: Relevance
“…In particular, Agu et al (2002) and Yang et al (2008) showed that decreased expression of endothelin-1 (ET-1), in combination with a decreased number of endothelin-B receptors, is a factor responsible for a reduction of the vasoconstrictor activity of veins and their varicose transformation [26,27]. Pietrzycka et al (2015) found that therapy with a micronized purified flavonoid fraction in female patients with a chronic venous disease (CVD) is accompanied by an increase in ET-1 levels, while the level of tumor necrosis factor-α (TNF-α) decreases, which indirectly indicates that ET-1 participates in the regulation of the venous tone in patients with CVD [28]. These data suggest that further research into the neurobiological aspects of venous pelvic pain is needed, which could allow one to evaluate the effect of other protein derivatives on the pathological processes taking place in the vein wall.…”
Section: Groupmentioning
confidence: 99%
“…In particular, Agu et al (2002) and Yang et al (2008) showed that decreased expression of endothelin-1 (ET-1), in combination with a decreased number of endothelin-B receptors, is a factor responsible for a reduction of the vasoconstrictor activity of veins and their varicose transformation [26,27]. Pietrzycka et al (2015) found that therapy with a micronized purified flavonoid fraction in female patients with a chronic venous disease (CVD) is accompanied by an increase in ET-1 levels, while the level of tumor necrosis factor-α (TNF-α) decreases, which indirectly indicates that ET-1 participates in the regulation of the venous tone in patients with CVD [28]. These data suggest that further research into the neurobiological aspects of venous pelvic pain is needed, which could allow one to evaluate the effect of other protein derivatives on the pathological processes taking place in the vein wall.…”
Section: Groupmentioning
confidence: 99%
“…Также применение МОФФ за 2 нед до склеротерапии и через 2 мес после нее приводит к снижению уровня гистамина, С-реактивного белка, ИЛ-1 и других маркеров воспаления у пациентов с легкой формой ХВН. Эти эффекты особенно важны, так как избыточный окислительный стресс (низкие соотношения антиоксидантных ферментов) приводит к чрезмерной выработке радикальных форм кислорода у больных с ХВН, что способствует активации лейкоцитов, процессов воспаления и повреждению эндотелия [9].…”
Section: микронизированная очищенная флавоноидная фракция (мофф)unclassified
“…Лечение МОФФ за 2 недели до и через 2 месяца после склеротерапии у пациентов с ХЗВ (С1) приводило к снижению уровня гистамина, С-реактивного белка, ИЛ-1, ФНО-α и VEGF в образцах венозной крови [76]. Прием МОФФ в течение 12 недель приводил к снижению концентрации эндотелина-1 и ФНОα в крови и увеличению активности антиоксидантных систем у женщин с ХЗВ [87]. Кроме того, доказано, что МОФФ ингибирует функцию тромбоцитов [77].…”
Section: микронизированная очищенная фракция флавоноидов (мофф)unclassified